Strategi Capacity Building Dalam Meningkatkan Kemampuan Aparatur Pemerintahan Nagari Di Nagari Persiapan Tanjung Beringin Utara Dan Selatan Kabupaten Pasaman - Novi Andzo Silalahi; Dt. Maani Karjuni (Jurnal Teori dan Riset Administrasi Publik, 2021)
This research is motivated by the lack of capacity of the nagari government apparatus in terms of organizational learning due to the lack of capacity building activities carried out both internally and from the local district government. Therefore, an active role for the district government is needed in addressing this matter. The purpose of this study is to describe the Capacity Building Strategy in Improving the Capability of Nagari Government Apparatus in Nagari Preparation for North and South Tanjung Beringin, Pasaman Regency, to identify the inhibiting factors of Capacity Building Strategy in Improving the Capability of Nagari Government Apparatus in Nagari Preparation for North and South Tanjung Beringin, Pasaman Regency. This research was processed using a qualitative approach with a descriptive method, this research was carried out at the Office of the Wali Nagari Preparation of North and South Tanjung Beringin, Lubuk Attitude District. Data collection techniques were carried out through observation, interviews and documentation. Based on the results of research and discussion, it was found that the Capacity Building Strategy in Improving the Capability of Nagari Government Apparatus can be said to be not optimal because it is only carried out through training organized by the Pasaman Regency Community Empowerment Service with a period of once a year. In its implementation, there are still many obstacles faced by the Department of Community Empowerment and the Preparation Nagari of North and South Tanjung Beringin, Pasaman Regency.